Opportunistic Screening for Detection and Socio-epidemiological Risk Assessment of Oral Cancer Patients in Rural Jodhpur, India - Meena, Jitendra Kumar; Verma, Anjana; Upadhyay, Sandeep Kumar (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Globally, India has a high burden (20%) of oral cancer with 1% prevalence of premalignant lesions. Most cases are attributed to modifiable risk factors such as substance abuse (tobacco and alcohol), dietary deficiencies, and environmental exposures (solar radiation and air pollution) aggravated by delayed detection and care especially in rural areas. Objective: The objective of the study was to study the risk factors of oral cancer pathogenesis among the rural residents of Jodhpur, India, through opportunistic oral screening approach at primary care facilities. Methodology: An unmatched case–control study was done at two randomly chosen rural health centres in Jodhpur, India. A total of 84 cases and 168 controls were included during 6 months study period (2016). Randomly selected outpatient department attendees were interviewed and screened for oral cancer and premalignant lesions. A structured questionnaire interview along with comprehensive oral, head and neck examination was conducted. Data were analyzed using multivariate logistic regression, and confidentiality of data was maintained. Results: The majority of the study participants were rural residents (82.9%) with poor socioeconomic status. Opportunistic oral screening revealed a variety of cancerous and precancerous lesions. Most common case pathologies were submucosal fibrosis (40.5%), inadequate mouth opening (35.7%), cheek bites (28.6%), leukoplakia (23.8%) etc. Multivariate analysis suggested that tobacco intake (adjusted odds ratio = 13.6, P ≤ 0.01) dietary deficiency (7.4, <0.01), oral sepsis (7.0, <0.01), oral lesions (6.8, <0.01), and sun radiation exposure (9.5, <0.01) were significantly associated with oral cancer pathology. Conclusion: The study provides strong evidence that tobacco, dietary deficiency, oral sepsis and lesions, and sun radiation exposure are independent risk factors for oral cancer. It also reiterates the importance and application of opportunistic oral cancer screening at primary care level.
Keywords: Case control; India; NPCDCS; Opportunistic screening; Oral cancer; Oral pathology; Tobacco